Experimental study of a virtual allowables approach for the design of composite aircraft structures. (July 2021) - Starace, F; Orlando, SD; Guida, M; Marulo, F
Statistically derived allowables are representative for the behavior of a composite material system in a given structural context where data variability needs to be contemplated. In particular, they define the strength of the material as characterized by various coupon tests according to ASTM standard procedure subjected to the actual manufacturing process and layup stacking sequences. The current paper presents a detailed comparison between virtual allowables predictions obtained using MSC Digimat and the experimentally determined values of a certified material backed up by a 3x2x3 (batch/panel/specimen) stochastic approach. Tests generate the required data for building material model ab initio of carbon fibers reinforced epoxide resin in form of 2x2 twill woven fabric used for qualifying an innovative composite wing for the Next Generation Tilt Rotor (NGCTR). Numerical models of in-plane tension, compression and shear test methods have been assembled along with an associated material model allowing numerical predictions to be validated with the coupon level experimental results as final purpose. Standard statistical model has been adopted in order to include material and manufacturing process variabilities to define B-basis allowables. The calibrated statistical FEM method performed for different layup configurations have been used to fully characterize the mechanical behavior of the analyzed CFRP material and to predict performances for thicker laminates.